GERMAN LANGUAGE COMPOSITES IN HERMAN HESSE’S NOVEL SIDDHARTA AND THEIR CORRESPONDENCES IN THE INDONESIAN LANGUAGE - Sulis Triyono (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2017)
This study aims to describe forms and meanings of German language composites and their correspondences in the Indonesian language. This was a qualitative descriptive study. The data were in the form of composites in German sentences in Herman Hesse’s novel Siddharta and its Indonesian translation by Hedy Holzwarth.The data were collected through the reading and writing technique. They were analyzed by the comparison and distribution techniques. The results of the study are as follows. First, there are 268 forms of composites, consisting of the Nullkonfix form, comprising a combination of noun+noun with a total of 161, a combination of adjective+noun with a total of 5, Konfixbeteiligung /-s/ (22 words), Konfixbeteiligung /-n/ (49 words), Konfix beteiligung /-en/ (6 words), Konfixbeteiligung /-er/ (17 words), and Konfixbeteiligung /-r/ (5 words). Second, German language composites are formed through the derivational and inflectional processes. A word formation functions as an attribute in a composite. In the Indonesian language, it is formed through an affixation process. Therefore, it can be concluded that German and Indonesian language composites have similar processes and meaning correspondences.Keywords: German and Indonesian language composites, correspondences